Mass Multiplication of Gymnema sylvestre (Retz.) R. Br. ex Schult. Through In vitro Shoot Organogenesis from Callus (Plant Tissue Culture and Biotechnology, 2020)
For large scale production through shoot organogenesis from callus, seeds of Gymnema sylvestre were cultured on MS containing various concentrations of 2,4-D. An optimum callusing (62.40%) was observed on MS with 1.5 mg/l 2,4-D. Upon transfer to multiplication medium, the calli multiplied 2.5 times in 45 days. The calli were then tested for shoot induction and an optimum result in terms of both per cent response (52.04%) and an average number of shoots (47.2) were observed on MS supplemented with 1.0 mg/l BAP. Maximum shoot elongation was obtained on 0.5 mg/l Kn and best rooting took place on half strength MS with 0.5 mg/l IBA. This protocol can be followed for the large scale in vitro multiplication of G. sylvestre.Plant Tissue Cult. & Biotech. 30(1): 27-32, 2020 (June)